Next Generation AI Driven Security and Analytics Framework for Cloud Native Enterprise Systems Financial Platforms and IoT Infrastructure (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The proliferation of cloud-native enterprise systems, financial platforms, and IoT infrastructure has revolutionized digital operations but simultaneously exposed organizations to increasingly sophisticated cyber threats. Traditional security measures are often insufficient to detect, predict, and mitigate dynamic attacks across distributed environments. This study proposes a next-generation AI-driven security and analytics framework designed to enhance resilience, real-time threat detection, and intelligent decision-making for modern enterprise ecosystems. Leveraging advanced machine learning, deep learning, and behavioral analytics, the framework continuously monitors network traffic, transaction data, and IoT device activity to detect anomalies, predict cyber risks, and automate response mechanisms. Cloud-native technologies, including microservices, containerization, and orchestration platforms, ensure scalability, high availability, and operational flexibility. The framework also incorporates zero-trust security principles, identity and access management, and intelligent data governance to maintain regulatory compliance and protect sensitive information. By integrating predictive analytics with AI-driven security operations, the proposed architecture enables proactive threat mitigation, minimizes operational disruption, and enhances enterprise resilience. This research highlights the role of AI-enhanced security analytics in securing distributed and heterogeneous infrastructures, offering a holistic framework capable of addressing the evolving cyber threat landscape across cloud-native financial platforms and IoT-enabled enterprise systems.
Keywords: AI-driven security; Cloud-native architecture; Enterprise analytics; Financial platform protection; IoT security; Real-time threat detection; Predictive cybersecurity; Zero-trust access control; Intelligent data governance; Cyber resilience